고객의 시간 지향성: 소매업체에서의 서비스 편의성과 쇼핑 성과의 관계에 대한 조절효과 - 김미정; 박철주; Kim, Mi-Jeong; Park, Chul-Ju (Journal of distribution science, 2016)
Purpose - Understanding how service convenience drives shopping performance is imperative for retailers such as department and large discount stores. Retailers have to enhance shopping productivity by reducing the costs of shopping, as convenience triggers customers' perceived shopping value, leading to customer satisfaction, and ultimately patronage behavior. Consumers, generally considering time as a scarce resource, are more sensitive to the time costs of tasks in regard to shopping trip, differently from forming perceptions of convenience in time orientation. Therefore, this study attempts to examine the moderating effects of consumers' time orientation on the relationships among service convenience of retailers and shopping performances such as shopping value and service performances. Research design, data, and methodology - The department and discount store chains were chosen as the point of analysis in this study. Data were collected from a survey of real-life consumers and all respondents were screened to ensure only those who had visited in the department and discount store chains within past six month prior to the day of data collection. Out of 600 self-reported surveys that were distributed, a total of 530 responses were returned and after excluding 20 incomplete responses, the final sample size was 510. The three hypotheses were proposed and tested in this study. The one hypothesis was on the moderating effects of time orientation for the effects of service convenience on shopping value (hedonic and utilitarian shopping value). The other two hypotheses were on the comparisons between high and low time-oriented customers with the effects in shopping value from service performance. Hierarchical moderated regression analysis was used to test the hypotheses. Results - The results suggest that the effect of service convenience on utilitarian shopping value and the positive effect of utilitarian shopping value on customer satisfaction are greater in low time orientation than high time orientation customers. Conversely, when customers are highly oriented toward time, the effects of hedonic shopping value on customer satisfaction and revisit intention are greater than for customers who are lowly oriented toward time. Conclusions - This study has two-fold significance. First, this study contributes to the consumer behavior and services marketing literature by incorporating customers' time orientation into the service convenience-shopping performance. Although the effect of service convenience on shopping performance might differ from customers' perceptions concerning shopping, there has been little investigation or comparison between customers' perception on time. This study is a first attempt to consider how the effects of service convenience on shopping value and service performance vary with differing levels of customers' time orientation. This study advances prior studies by showing that the service convenience-shopping value and service convenience-service performance relationships vary across different combinations of the customer's time orientation. The findings of this study suggest that the retailers need to enhance the experiential aspects of the stores for their high time-oriented customers. Conversely, for the low time-oriented customers, the retailers should boost the visual distinctiveness and ease of store navigation.